Early microbial succession in redeveloping dental biofilms in periodontal health and disease - Teles, F. R.; Teles, R. P.; Uzel, N. G.; Song, X. Q.; Torresyap, G.; Socransky, S. S.; Haffajee, A. D. (Journal of periodontal research, 2012)
Teles FR, Teles RP, Uzel NG, Song XQ, Torresyap G, Socransky SS, Haffajee AD. Early microbial succession in redeveloping dental biofilms in periodontal health and disease. J Periodont Res 2012; 47: 95–104. © 2011 John Wiley & Sons A/S Background and Objective:  The development of dental biofilms after professional plaque removal is very rapid. However, it is not clear whether most bacterial species return at similar rates in periodontally healthy and periodontitis subjects or if there are differences in bacterial recolonization between supragingival and subgingival biofilms in periodontal health and disease. Material and Methods:  Supragingival and subgingival plaque samples were taken separately from 28 teeth in 38 healthy and 17 periodontitis subjects immediately after professional cleaning. Samples were taken again from seven teeth in randomly selected quadrants after 1, 2, 4 and 7 d of no oral hygiene and analyzed using checkerboard DNA–DNA hybridization. The percentage of DNA probe counts were averaged within subjects at each time‐point. Ecological succession was determined using a modified moving‐window analysis. Results:  Succession in supragingival biofilms from subjects with periodontitis and from healthy individuals was similar. At 1 d, Streptococcus mitis and Neisseria mucosa showed increased proportions, followed by Capnocytophaga gingivalis, Eikenella corrodens, Veillonella parvula and Streptococcus oralis at 1–4 d. At 4–7 d, Campylobacter rectus, Campylobacter showae, Prevotella melaninogenica and Prevotella nigrescens became elevated. Subgingival plaque redevelopment was slower and very different from supragingival plaque redevelopment. Increased proportions were first observed for S. mitis, followed by V. parvula and C. gingivalis and, at 7 d, by Capnocytophaga sputigena and P. nigrescens. No significant increase in the proportions of periodontal pathogens was observed in any of the clinical groups or locations. Conclusion:  There is a defined order in bacterial species succession in early supragingival and subgingival biofilm redevelopment after professional cleaning.